PENDIRIAN BUMDES DENGAN AKTA NOTARIS BERBADAN HUKUM PERKUMPULAN - Steven Federik; Tjempaka Tjempaka (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
The deed of establishment of the Margakaya Bangkit BUMDes association has met the legality requirements as the deed specified in Article 1868 in conjunction with Article 1338 of the Criminal Code because it was made based on statutory provisions and the applicant's will, so that the implication has legal force and provides assurance and legal protection for the required account opening process the bank. However, it is a mistake to consider the establishment of BUMDes by making a notary deed, let alone an association deed, so based on Article 16 (1) letter a UUJN jo Article 16 Paragraph (11) the actions of the notary TN, SH, MH in carrying out their duties are not careful in understanding the provisions of the BUMDes legislation which should not have been written off because the Village Regulation is sufficient as a legal entity. In addition, notaries also violate Article 3 point 5 in conjunction with Article 6 of the Notary Code of Ethics. As a notary, he must have extensive knowledge including the problem of establishing BUMDes that do not need a notary deed. For violations of UUJN and the Code of Ethics, notary TN, SH, MH, can be subject to administrative sanctions with a written warning or a warning from the notary organization